Lean production system: compatible with Malaysian culture - Ng, Siew Imm; Cha, Ck; Sambasivan, Murali; Abd Rahman, Azmawani (Emerald Publishing, 2021)
Theoretical basis: An instructor could link the case to lean production principles and Kurt Lewin’s change management model, key reading materials on these theories are, namely,  Lewin, K (1947) Frontiers in group dynamics: concept, method and reality in social science; equilibrium and social change. Human Relations 1(1): 5–41  Stewart, J. (2012). The Toyota Kaizen continuum: a practical guide to implementing lean. Boca Raton, FL: CRC Press. Wickramasinghe, V. and Wickramasinghe, G. L. D. (2020). Effects of human resource management practices, lean production practices and lean duration on performance. The International Journal of Human Resource Management, 31(11), 1467–1512. Research methodology: This case was developed from both primary and secondary sources. The primary source included three face to face meetings with Mr CK in University Putra Malaysia (two meetings) and WSAE factory (Rawang, Malaysia – one meeting), respectively. Interviewed three workers at Rawang factory. The secondary source was taken from the company website and company reports. Case overview/synopsis: Dr Wan, the Chief Executive Officer of WSA Engineering Sdn Bhd (WSAE) accepted the invitation from Small Medium Industries Development Corporation to participate in a Malaysian-Japanese Industry Cooperation program that focused on Lean Production System (LPS). Dr Wan was worried about Malaysia’s culture incompatible with Japanese-originated LPS. The case shares how the organization and behavioral change took place, for LPS buy-in. Successes and challenges WSAE faced in the 10-year journey of implementing LPS were elaborated. Complexity academic level This case was written for use in an operations management course, on the topic of lean production. It can also be used as a training material targeting the operation managers of a manufacturing company aiming to implement lean production or any change management process.